2021
DOI: 10.1177/10915818211002487
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Public Health Effects of Polycyclic Aromatic Hydrocarbon Compounds in Sub-Saharan Africa: A Systematic Review

Abstract: Background and Aim: In order to achieve improved global health, environmental health risks that could affect this goal have to be reduced as much as possible. This review thus aimed at determining the exposure levels, health risk assessments, and public health effects of polycyclic aromatic hydrocarbons (PAHs) in sub-Saharan Africa (SSA). This review was developed using guidelines provided for Preferred Reporting Items for Systematic Review and Meta-Analysis. Search was done on Google Scholar, Scopus, and PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 98 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Due to the heterogeneity in the methodologies utilized in the different studies to assess the exposure and outcome variables, we did not do a meta-analysis. This heterogeneity included differing pollutants, varying sites of exposure, sources, and application of varying study designs [58]. Therefore, this systematic review showed the diversities in the methodologies used for evaluating outcomes in relation to exposure variables.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the heterogeneity in the methodologies utilized in the different studies to assess the exposure and outcome variables, we did not do a meta-analysis. This heterogeneity included differing pollutants, varying sites of exposure, sources, and application of varying study designs [58]. Therefore, this systematic review showed the diversities in the methodologies used for evaluating outcomes in relation to exposure variables.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the type of wood has a significant influence on the increase of PAH contents in smoked foods. Similarly, the use of cartons during the smoking process could modify the photosensitive properties of PAHs and cause their accumulation in foods [ 26 ]. In addition, this is the fact that the PAH content in smoked products varies and depends on environmental factors such as the presence or absence of light or oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are a group of chemicals that are common air pollutants originating from the incomplete combustion of organic matter. Exposure to PAHs has been reported to be associated with several health outcomes [1] such as diabetes [2], cardiovascular diseases [3], respiratory diseases [4, 5], and cancer [6]. PAHs could be easily absorbed by fatty tissues and accumulated through long‐term exposure or the food chain [7], resulting in metabolic disorders by disrupting lipid metabolism [8].…”
Section: Introductionmentioning
confidence: 99%